2014
DOI: 10.1186/1880-5981-66-56
|View full text |Cite
|
Sign up to set email alerts
|

Highly varying daytime sodium airglow emissions over an equatorial station: a case study based on the measurements using a grating monochromator

Abstract: A case study is performed to investigate the probable reasons behind substantial daytime sodium (Na) D 1 airglow intensity (589.6 nm) variations measured using a ground-based monochromator during the three near consecutive days of February 2007 from Trivandrum (8.5°N, 77°E), India. The roles of both the resonance fluorescence and the chemistry have been considered in this study. It appears that fluorescence plays only a minor role towards the observed five to nine times of large intensity variations among thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Such temperature fluctuations can influence the mesospheric chemistry, which can affect the strength of sporadic neutral layers as a result of ion-neutral coupling. The Na dayglow intensity variations observed for a few days from Trivandrum (India), a lowlatitude station, have been attributed to chemistry (Hossain et al, 2014). Another factor mentioned previously that can affect the strength of neutral sporadic activity can be due to inhomogeneity in the medium or advection, but that alone cannot explain why the minor species like Na show stronger sporadic layer as compared to one of the major metals like Fe relative to their main or permanent layers.…”
Section: Discussionmentioning
confidence: 88%
“…Such temperature fluctuations can influence the mesospheric chemistry, which can affect the strength of sporadic neutral layers as a result of ion-neutral coupling. The Na dayglow intensity variations observed for a few days from Trivandrum (India), a lowlatitude station, have been attributed to chemistry (Hossain et al, 2014). Another factor mentioned previously that can affect the strength of neutral sporadic activity can be due to inhomogeneity in the medium or advection, but that alone cannot explain why the minor species like Na show stronger sporadic layer as compared to one of the major metals like Fe relative to their main or permanent layers.…”
Section: Discussionmentioning
confidence: 88%
“…There are a very limited number of studies which have been reported in the literature on VER of sodium D line airglow emission [Clemesha et al, 1995;Hecht et al, 2000;Sarkhel et al, 2010;Plane et al, 2012;Hossain et al, 2014]. Most of the VER profiles have been derived from either rocket measurement intensity or ground-based airglow intensity.…”
Section: 1002/2015ja022031mentioning
confidence: 99%
“…The ablation of meteors at the mesopause region results in the formation of the sodium layer [Plane, 1991]. Due to the fact that it has a large scattering cross section and also that it acts as a tracer for the thermal and dynamical states of the atmosphere in this altitude range [Plane et al, 1999;Griffins et al, 2001], the mesospheric sodium has been studied extensively among all meteoric metals [Kirchhoff et al, 1981;Kirchhoff , 1986;Plane, 1991;Clemesha et al, 1995;Hecht et al, 2000;Plane et al, 1999;Griffins et al, 2001;Slanger et al, 2005;Fan et al, 2007;Clemesha et al, 2010;Plane et al, 2012;Hossain et al, 2014]. The peak density layer exists at around 90 km.…”
Section: Introductionmentioning
confidence: 99%